Cosmetic Dermatology in Pregnancy and Lactation: A Risk–Benefit Framework for Clinical Practice - Timea Kovacs; Umer Nadir; Michael Goldenberg; Thomas E. Rohrer; Deirdre Hooper; George M. Jeha; Stanislav N. Tolkachjov (International Journal of Dermatology, 2026)
ABSTRACT Cosmetic dermatologic products and procedures are increasingly utilized by women of reproductive age, including those who are pregnant or lactating. Pregnancy and lactation are associated with hormonal, vascular, and immunologic changes that may alter skin biology, cutaneous absorption, and susceptibility to adverse effects. Despite growing demand, clinicians frequently face uncertainty when counseling patients regarding cosmetic interventions, as high‐quality safety data and formal guidelines remain limited. This review summarizes the available evidence and practical counseling considerations for commonly used topical agents, chemical peels, injectable neuromodulators and fillers, lasers and light‐based therapies, and energy‐based devices, while proposing a practical counseling framework that distinguishes recommendations between pregnancy and lactation. This distinction is critical, as these states are often conflated despite differing pharmacokinetic profiles and safety considerations. Unlike a systematic review, this narrative review qualitatively synthesizes the available literature while emphasizing clinically applicable counseling. The published literature largely consists of observational studies, case reports, and extrapolation from nonpregnant populations, reflecting the ethical and practical limitations of conducting controlled trials in these populations. Overall, pregnancy and lactation should not be approached as equivalent counseling states. During pregnancy, elective cosmetic interventions are deferred, and pregnancy‐related physiologic changes may alter both treatment risk and cosmetic outcome. During lactation, many interventions may be considered following individualized risk assessment when systemic exposure is expected to be minimal, and treatment sites avoid direct infant contact. Counseling should emphasize conservative management, transparent discussion of uncertainty, and shared decision‐making tailored to the patient's reproductive status and treatment goals. image